"Fabryki zboża, mięsa i mleka". Państwowe Gospodarstwa Rolne w województwie zielonogórskim w latach 1950-1956. Wprowadzenie do problematyki = "Grain, meat and milk factory". State Agricultural Farms in Zielona Gora Province during 1950-1956. Introduction - Koteluk, Daniel (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
According to government calculations, State Agricultural Farms, modeled on the Soviet sovkhozes, were supposed to, as a part of a six-year economic plan, accomplish specific assignments. The Party expected them to be viable socialist enterprises providing the population with basic agricultural products, as well as ideological centers influencing the peasants in order for them to accept socialist agricultural production.
Keywords: kolektywizacja; komunizm - Polska; Państwowe Gospodarstwa Rolne; województwo zielonogórskie; Plan 6-letni; deficyt; collectivization; State Agricultural Farms; six-year economic plan; deficit